(2+1)-dimensional gravity in Weyl integrable spacetime. (7th October 2015) - Aguilar, J E Madriz; Romero, C; Fonseca Neto, J B; Almeida, T S; Formiga, J B
Abstract: We investigate (2+1)-dimensional gravity in a Weyl integrable spacetime (WIST). We show that, unlike general relativity, this scalar-tensor theory has a Newtonian limit for any dimension and that in three dimensions the congruence of world lines of particles of a pressureless fluid has a non-vanishing geodesic deviation. We present and discuss a class of static vacuum solutions generated by a circularly symmetric matter distribution that for certain values of the parameter ω corresponds to a spacetime with a naked singularity at the center of the matter distribution. We interpret all these results as being a direct consequence of the spacetime geometry.